2022
DOI: 10.1021/acsami.2c13304
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry-Induced Ordered Assembly of a Naphthobisthiadiazole-Based Nonfused-Ring Electron Acceptor Enables Efficient Organic Solar Cells

Abstract: Nonfused-ring electron acceptors (NFREAs) have received increasing attention for use in organic solar cells (OSCs) because of their synthetic simplicity and tunable optical spectra. However, their fundamental molecular interactions and the mechanism by which they govern the property–function relations of OSCs remain elusive. Here, to investigate the effects of the structural symmetry of NFREAs, two acceptor–donor–acceptor′–donor–acceptor (A–D–A′–D–A)-type NFREAs, 2,2′-(((naphtho[1,2-c:5,6-c′]bis[1,2,5]thiadiaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…10 In addition, non-fused-ring electron acceptors (NFREAs) with A-D-A 0 -D-A-type structures have been investigated because of their facile synthesis. [17][18][19][20] Chen et al reported DF-PCIC, the first NFREA-based OSC with a PCE greater than 10%, in 2018. 21 DF-PCIC exhibits a nearly planar structure as a result of HÁ Á ÁF noncovalent interaction locks between its 2,5difluorobenzene core and cyclopentadithiophene (CPDT) D units; thus, its conjugation degree is high.…”
Section: Introductionmentioning
confidence: 99%
“…10 In addition, non-fused-ring electron acceptors (NFREAs) with A-D-A 0 -D-A-type structures have been investigated because of their facile synthesis. [17][18][19][20] Chen et al reported DF-PCIC, the first NFREA-based OSC with a PCE greater than 10%, in 2018. 21 DF-PCIC exhibits a nearly planar structure as a result of HÁ Á ÁF noncovalent interaction locks between its 2,5difluorobenzene core and cyclopentadithiophene (CPDT) D units; thus, its conjugation degree is high.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the Eloss$E_{\text{loss}}$ of the Y6:PCBM‐based devices, we analyzed the Eloss$E_{\text{loss}}$ using Fourier‐transform photocurrent spectroscopy (FTPS) and EL measurements ( Figure a). The Eloss$E_{\text{loss}}$ of a device can be divided into three terms [ 28–30 ] Eloss=(EgqVOCSQ)+(qVOCSQqVOCrad)+(qVOCradqVOC)=ΔE1+ΔE2+ΔE3$$E_{\text{loss}} = \left(\right. E_{\text{g}} - q V_{\text{OC}}^{\text{SQ}} \left.\right) + \left(\right.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that PCBM forms smaller aggregates than Y6 both in blends and in pristine films. [ 28 ] Thus, the smooth surface morphologies of the Y6:PCBM‐based blends with >20% PCBM might result from a concurrent increase in the number of PCBM aggregates and a decrease in the number of Y6 aggregates. The combination of GIWAXS and AFM results confirms that PCBM is mainly dispersed in the mixed phase when the PCBM content is <20% but forms aggregates when the PCBM content is >20%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We note that the overall photovoltaic performances of the cells derived from these two acceptors are moderate, and they might need to be integrated with more appropriate electron-donating polymers to enhance the photovoltaic parameters. 44,45 The detailed photovoltaic parameters are summarized in Table 2. The slightly higher J SC of the device based on NTIC-4Cl can be further confirmed by the current density values integrated from the external quantum efficiency (EQE) spectra (Fig.…”
Section: Photovoltaic Performancesmentioning
confidence: 99%